2009
DOI: 10.1007/s00421-009-1292-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strength training with eccentric overload on muscle adaptation in male athletes

Abstract: In classic concentric/eccentric exercise, the same absolute load is applied in concentric and eccentric actions, which infers a smaller relative eccentric load. We compared the effects of 6 weeks of classic concentric/eccentric quadriceps strength training (CON/ECC, 11 subjects) to eccentric overload training (CON/ECC+, 14 subjects) in athletes accustomed to regular strength training. The parameters determined included functional tests, quadriceps and fibre cross-sectional area (CSA), fibre type distribution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 58 publications
7
113
1
6
Order By: Relevance
“…Typically increases in muscle cross sectional area are observed in humans following resistance training programmes of 6-16 weeks duration, with the extent of hypertrophy from 7.5 to 25% depending on the study participants, muscle type studied and exercise regime (McCall et al 1996;Kosek et al 2006;Holm et al 2008;Friedmann-Bette et al 2010). In vivo animal studies have also demonstrated robust hypertrophic responses to muscle loading (Goldberg 1967;Goldspink et al 1995).…”
Section: Alterations In Muscle Phenotype and Metabolismmentioning
confidence: 95%
“…Typically increases in muscle cross sectional area are observed in humans following resistance training programmes of 6-16 weeks duration, with the extent of hypertrophy from 7.5 to 25% depending on the study participants, muscle type studied and exercise regime (McCall et al 1996;Kosek et al 2006;Holm et al 2008;Friedmann-Bette et al 2010). In vivo animal studies have also demonstrated robust hypertrophic responses to muscle loading (Goldberg 1967;Goldspink et al 1995).…”
Section: Alterations In Muscle Phenotype and Metabolismmentioning
confidence: 95%
“…The optimal intensity of eccentric training programs is not yet clear. Some authors recommend that intensity should be high to provide the stimulus necessary to produce further adaptations (Hortobagyi et al 1996;Brughelli and Cronin 2007;Friedmann-Bette et al 2010), while others have found that the protective effect of eccentric training may be observed even using low resistance (Lavender and Nosaka 2008;Chen et al 2010). If strength gain is required to address a strength deficit, eccentric actions should be overloaded between 20 % and 80 % beyond the maximal isometric strength.…”
Section: Training Parametersmentioning
confidence: 95%
“…Training where ECC actions were overload (ECC overload [EO] training), performed with more load than during CON action it was verified after training an increase on the size of type IIX fibres 7 , a higher increase at isokinetic and isometric force production 8 and higher neuromuscular activation [8][9][10] . Owing to the importance of ECC actions in neuromuscular activation 11 and the benefits of EO training, machines have been developed to increased load during the ECC action [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%